A COMPARATIVE STUDY OF TRADITIONAL AND MODERN APPROACHES IN ENGLISH LANGUAGE TEACHING METHODOLOGY (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article explores the comparison between traditional and modern approaches in English language teaching (ELT). It provides a comprehensive analysis of grammar-translation, direct, and audiolingual methods from traditional ELT, contrasted with communicative language teaching (CLT), task-based learning (TBL), and content-based instruction (CBI) from modern approaches. The discussion focuses on how each methodology meets the needs of learners in different contexts, highlighting the advantages and limitations of each approach.